Binding Kinetics and Pathways of Ligands to GPCRs. (August 2017) - Strasser, Andrea; Wittmann, Hans-Joachim; Seifert, Roland
Abstract : Previously, drugs were developed focusing on target affinity and selectivity. However, it is becoming evident that the drug–target residence time, related to the off-rate, is an important parameter for successful drug development. The residence time influences both the on-rate and overall effectiveness of drugs. Furthermore, ligand binding is now appreciated to be a multistep process because metastable and/or intermediate binding sites in the extracellular region have been identified. In this review, we summarize experimental ligand-binding data for G-protein-coupled receptors (GPCRs), and their binding pathways, analyzed by molecular dynamics (MD). The kinetics of drug binding to GPCRs are complex and depend on several factors, including charge distribution on the receptor surface, ligand–receptor interactions in the binding channel and the binding site, or solvation. Trends: Due to recent efforts in the development of fast computers, MD simulations and related techniques allow calculation of the binding pathways of ligands and estimation of rate constants. Identification of metastable binding sites may be useful for the development of dimeric or bivalent compounds that can bind to orthosteric, metastable binding sites, which may result in an increased affinity. Considering binding kinetics in the development of new drugs may lead to drugs with increased effectiveness.